Ta’ṡīr Istikhdām aṭ-Ṭarīqah as-Siyāqiyyah Fī Ta`līm Mahārah al-Kalām (Baḥṡ Tajrībī Fī aṣ-Ṣaff al-Awwal “Safīr” Bi al-Madrasah al-Mutawassiṭah al-Mutakāmilah ad-Durrah Mārilān) - Shalini Shalini (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
The formulation of the problem in this research is what students' abilities are towards learning speaking skills using the method contextual and without using it in class VII